Simulating Smart Cities Under Different Scenarios and Factors - Hussein, Yaser Mohammed; Hamze, Mohamad Tawfik (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
In this research, we suggest building or utilizing a virtual environment of a smart city where fixed and mobile sensors are arranged in a certain way, using particular movement models and techniques for transmitting and sharing data via the virtual city. This proposal proposes to carry out several experiments for various movement models, such as:(Individual Mobility Model,Exponential movement model and Rayleigh Flight movement model), A specific data distribution (Gaussian, Littice, Power-law, Exponential) and a certain data routing methodology (Spray and Wait, Probabilistic Flooding, and Epidemic) were used to examine the impact of this on the use of network resources. In this proposal, we also want to look at the usage of various resources, including electricity and data. A movement model, an item distribution strategy, and a data routing protocol were all combined to create each experiment that was intended to be conducted in this proposal. All submitted experiments will ultimately be compared to one another, and recommendations that assist the research and design community in conserving network resources will be made. the findings show that the traffic models that were used with mobile nodes are considered one of the important factors in determining the consumption of network resources. In addition to the influence of traffic models on the consumption of network resources, algorithms and methods of routing data also have an impact. The Human Mobility Model, which accurately expresses human movement behavior, is considered one of the most stable models in terms of performance.